2016
DOI: 10.1093/nar/gkw098
|View full text |Cite
|
Sign up to set email alerts
|

Homologous DNA strand exchange activity of the human mitochondrial DNA helicase TWINKLE

Abstract: A crucial component of the human mitochondrial DNA replisome is the ring-shaped helicase TWINKLE—a phage T7-gene 4-like protein expressed in the nucleus and localized in the human mitochondria. Our previous studies showed that despite being a helicase, TWINKLE has unique DNA annealing activity. At the time, the implications of DNA annealing by TWINKLE were unclear. Herein, we report that TWINKLE uses DNA annealing function to actively catalyze strand-exchange reaction between the unwinding substrate and a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Indeed, TWINKLE overexpression in WT mice led to an increased level of mtDNA rearrangements (see Supplementary Figure S6 in the original publication 48 ). In addition to its putative function as a helicase, TWINKLE has been shown to catalyze DNA recombination 49,50 . A recent study further demonstrated that strand exchange activity of TWINKLE requires 3-6 bp sequence homology 50 The one exception to this pattern is the autosomal polg mutations.…”
Section: Mammalian Mtdna Deletions Predominantly Exhibit Short and Mementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, TWINKLE overexpression in WT mice led to an increased level of mtDNA rearrangements (see Supplementary Figure S6 in the original publication 48 ). In addition to its putative function as a helicase, TWINKLE has been shown to catalyze DNA recombination 49,50 . A recent study further demonstrated that strand exchange activity of TWINKLE requires 3-6 bp sequence homology 50 The one exception to this pattern is the autosomal polg mutations.…”
Section: Mammalian Mtdna Deletions Predominantly Exhibit Short and Mementioning
confidence: 99%
“…In addition to its putative function as a helicase, TWINKLE has been shown to catalyze DNA recombination 49,50 . A recent study further demonstrated that strand exchange activity of TWINKLE requires 3-6 bp sequence homology 50 The one exception to this pattern is the autosomal polg mutations. POLG is the sole DNA polymerase present in mammalian mitochondria.…”
Section: Mammalian Mtdna Deletions Predominantly Exhibit Short and Mementioning
confidence: 99%
“…Thus, Twinkle’s ability to upregulate mitochondrial biogenesis can help to alleviate oxidative stress associated with cardiac dysfunction. Twinkle’s ability to catalyze homologous strand exchange and DNA branch-migration and its proposed role in recombinational repair and remodeling of stalled mitochondrial replication forks [42, 208] may be relevant to situations of elevated oxidative stress.…”
Section: Dna Helicases and The Metabolism Of Mitochondrial Oxidativelmentioning
confidence: 99%
“…To our knowledge, this and another study (34) published while ours was under revision are the first reported demonstrations that Twinkle possesses DNA branch migration activity of a D-loop, a DNA substrate the enzyme is likely to encounter during mtDNA replication. Collectively, the in vitro studies suggest that Twinkle may be capable of acting upon D-loop substrates by a combination of its branch migration and helicase activity, the latter not restricted to D-loops with pre-existing 5Ј singlestranded DNA tails.…”
Section: Discussionmentioning
confidence: 53%